Synthesis and characterization of TEMPO- and viologen-polymers for water-based redox-flow batteries. Issue 45 (30th October 2015) - Janoschka, T.; Morgenstern, S.; Hiller, H.; Friebe, C.; Wolkersdörfer, K.; Häupler, B.; Hager, M. D.; Schubert, U. S.
Abstract : Water-soluble polymers for application in polymer-based redox-flow batteries (pRFB) were synthesized and their properties were studied in detail. Abstract : Redox-flow batteries that employ redox-active polymers (pRFB) represent a novel energy storage technology requiring innovative materials. Polymers bearing a viologen unit ( N, N ′-dialkyl-4, 4′-bipyridines) or a TEMPO radical are synthesized. Acrylamide, poly(ethyleneglycol) methyl acrylates, di(ethylene glycol) methacrylate and 2-(methacryloyloxy)- N, N, N -trimethylethane ammonium chloride are studied as water-solubility-enhancing comonomers. The rheological and electrochemical properties of these polymers in aqueous solutions are evaluated, revealing poly(1-methyl-1′-(4-vinylbenzyl)-[4, 4′-bipyridine]-1, 1′-diium dichloride) (P2a ) and poly(4-methacryloyloxy-2, 2, 6, 6-tetramethylpiperidine-1-oxyl- co -2-(methacryloyloxy)- N, N, N -trimethylethane ammonium chloride) (P4e ) to be most suited as anode and cathode materials, respectively, for a pRFB.